Show a Threshold Effect in Response to Radiation - Michael Antosh; David Fox; Thomas Hasselbacher; Robert Lanou; Nicola Neretti; Leon N. Cooper (SAGE Publishing, 2014)
We investigate the biological effects of radiation using adult Drosophila melanogaster as a model organism, focusing on gene expression and lifespan analysis to determine the effect of different radiation doses. Our results support a threshold effect in response to radiation: no effect on lifespan and no permanent effect on gene expression is seen at incident radiation levels below 100 J/kg. We also find that it is more appropriate to compare radiation effects in flies using the absorbed energy rather than incident radiation levels.